Augmentation of Simplex Algorithm for Linear Programming Problem to Enhance Computational Performance - Azlan, N.A.A.N.; Saptari, A.; Mohamad, E. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Linear programming (LP) has been seen as a tool to solve problem in mathematical way with various methods to perform the solution. Simplex method is one of pioneer methods in dealing with linear problem in LP. It involves step-by-step works towards the solution in its algorithm. Due to this distinctiveness, it has brought up interest in others and few studies were done by researchers to come out with augmentation study in enhancing computational performance of Simplex method in terms of initialization, iteration and termination. In this paper, three studies were recognized in augmenting Simplex algorithm namely Basic Line Search Algorithm (BLSA),